Penyuluhan Investasi Keuangan Sederhana Siswa SMA Kristen Tunas Harapan Bogor - Rachmat, Taofiq (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2025)
Giving basic financial investment education as a service to the community was done for students at Tunas Harapan Christian High School in Bogor. The point of this activity was to teach them the basics of understanding money and investing while they are still in school. This program was carried out because students do not know much about handling their money and planning safe investments, and they often spend too much without a plan. The topics covered included learning about what investing is, the different ways to invest that people usually use (like stocks, bonds, mutual funds, gold, and savings accounts), looking at the risks and possible rewards, advice on starting to invest with a small amount of money, and common mistakes to avoid. The ways used to carry out this training included interactive talks, question and answer times, sharing stories, and showing information with PowerPoint slides. The students were guided to understand how saving money, investing safely, and reaching money goals in the future are all connected. The results of this activity showed that the students knew more about basic investing ideas, were aware of the risks, and could plan how to start managing their own money. With this education, it is hoped that students can develop good, thrifty, and planned money habits from an early age.